2009
DOI: 10.1002/lapl.200810137
|View full text |Cite
|
Sign up to set email alerts
|

LD-pumped passively Q-switched Nd:LuVO4laser with a GaAs output coupler

Abstract: By using GaAs as both a saturable absorber and an output coupler, a laser-diode pumped passively Q-switched Nd:LuVO 4 laser has been realized for the first time to our knowledge. The maximum laser output power of 1.91 W has been obtained at the incident pump power of 12.7 W, corresponding to an optical conversion efficiency of 15%. At this incident pump power, the minimum the pulse width of 3.8 ns has also been obtained at the pulse repetition rate of 952 kHz with peak power of 482 W.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Moreover, Nd:LuVO 4 crystal has a high damage threshold, and it is easy to process [19]. The research to output wavelengths involving 4174 cm -1 4157 cm -1 4094 cm -1 4074 cm -1 3982 cm -1 3926 cm -1 3900 cm -1 2176 cm -1 2140 cm -1 2065 cm -1 2028 cm -1 1990 cm -1 1969 cm -1 473 cm -1 270 cm -1 171 cm -1 118 cm -1 0 cm -1 Nd:LuVO 4 crystals were mostly focused at 1066 nm [20][21][22][23][24][25][26][27][28][29] and 1343 nm [30]. However, in all these studies the pumping is made in levels above the emitting level 4 F 3/2 of Nd 3+ , usually in 4 F 5/2 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Nd:LuVO 4 crystal has a high damage threshold, and it is easy to process [19]. The research to output wavelengths involving 4174 cm -1 4157 cm -1 4094 cm -1 4074 cm -1 3982 cm -1 3926 cm -1 3900 cm -1 2176 cm -1 2140 cm -1 2065 cm -1 2028 cm -1 1990 cm -1 1969 cm -1 473 cm -1 270 cm -1 171 cm -1 118 cm -1 0 cm -1 Nd:LuVO 4 crystals were mostly focused at 1066 nm [20][21][22][23][24][25][26][27][28][29] and 1343 nm [30]. However, in all these studies the pumping is made in levels above the emitting level 4 F 3/2 of Nd 3+ , usually in 4 F 5/2 .…”
Section: Introductionmentioning
confidence: 99%
“…3 show the pulse width W of the pure GaAs Q-switched laser and the doubly Qswitched lasers with different T 0 on incident pump power, which indicate that doubly passively Q-switched laser can generate the shorter pulse width compared with single GaAs Q-switched laser. The shortest pulse width of 4.18 ns and 5.42 ns at T 0 = 0.71 and T 0 = 0.81 are achieved at the incident pump power of 11.23 W. An et al have been studied a passively Q-switched Nd:LuVO 4 laser with a GaAs output coupler [23], they obtained the pulse width of 3.8 ns with the peak power of 482 W at the incident pump power of 12.7 W. The reason of the quite narrow pulse width of 3.8 ns is that they used much short cavity length of 4 cm. For the stability of the laser, our doubly passively Q-switched laser has the cavity length of 6.5 cm, which can obtain more symmetric pulse shape and higher peak power.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first appearance in 2002 [3], the new vanadate laser crystal, Nd:LuVO 4 , has attracted much attention because it owns many prominent advantages including large absorption and emission cross sections, high damage threshold, and is easy to process. These properties are favorable to make high efficiency DPSSLs, and in recent years the research and application on this material have covered many areas, such as near infrared laser [11][12][13][15][16][17][18], visible laser by frequency mixing [19][20][21][22][23], Q-switched laser [13,[24][25][26][27][28][29], mode-locked laser [30][31][32][33][34][35][36][37][38], and self-Raman frequency shifting [10,39]. Nevertheless, the research of J. Morikawa et al [40] has shown that the thermal conductivity of Nd:LuVO 4 crystal is obvious lower than the other two well-known vanadate crystals, Nd:YVO 4 and Nd:GdVO 4 .…”
Section: Discussionmentioning
confidence: 99%